PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE-OUTSIDE CIRCLE UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIK SISWA - BUDIARTI, CORY EKA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Generally the aim of this research is to describe student’s mathematics communication capability through the application of cooperative learning model inside-outside circle type. This research is especially aimed to reveal: 1) The process of mathematic learning in the classroom by using cooperative learning model inside-outside circle type, 2) The students response toward mathematic learning by using cooperative learning model inside-outside circle type, 3) Student’s cooperation in learning mathematic after applicated cooperative learning model inside-outside circle type, 4) the student’s mathematics communication capability after learning mathematics by using cooperative learning model inside-outside circle type. This research was conducted in SMP Islam Al-Falaah in academic Year 2022/2023. The method used in this study is the Classroom Action Research, which consists of four stages of planning, execution, observation, and reflection. The research instrument used is the observation sheet student’s mathematics communication capability, observation sheet student’s cooperation, the daily student journals, interview, and test of mathematic communication. Based on the results of observations, there was an increase in students' mathematical communication skills from cycle I to cycle II by 21.66%, and the results of students' mathematical communication ability tests at the end of each cycle from the initial score to the results of students' mathematical communication ability tests in cycle I was 22.19, while from cycle I to cycle II there was an increase of 10.81, it can be seen that learning using the inside-outside circle type cooperative learning model can improve students' mathematical communication skills. ABSTRAKSecara umum tujuan penelitian ini adalah untuk mendeskripsikan kemampuan komunikasi matematik siswa melalui penerapan model pembelajaran kooperatif tipe Inside-Ouside Circle. Secara khusus penelitian ini bertujuan untuk mengetahui 1) Proses pembelajaran matematika di kelas dengan menggunakan model pembelajaran kooperatif tipe Inside-Ouside Circle, 2) Respon siswa terhadap pembelajaran matematika dengan model pembelajaran kooperatif tipe Inside-Ouside Circle, 3) Kerjasama siswa dalam pembelajaran matematika setelah diterapkan model pembelajaran kooperatif tipe Inside-Ouside Circle, 4) kemampuan komunikasi siswa setelah pembelajaran matematika dengan model pembelajaran kooperatif tipe Inside-Ouside Circle. Penelitian ini dilakukan di SMP Islam Al-FalaahTahun Ajaran 2022/2023. Metode yang digunakan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK) yang terdiri dari empat tahap, yaitu tahap perencanaan, pelaksanaan, observasi, dan refleksi. Instrumen penelitian yang digunakan adalah lembar observasi kemampuan komunikasi matematik, jurnal harian siswa, wawancara, dan tes kemapuan komunikasi matematik. Berdasarkan hasil observasi terjadi peningkatan kemampuan komunikasi matematik siswa dari siklus I terhadap siklus II sebesar 21,66%, dan hasil tes kemampuan komunikasi matematik siswa di setiap akhir siklus dari skor awal terhadap skor hasil tes kemampuan komunikasi matematik siswa siklus I sebesar 22,19 sedangkan dari siklus I terhadap siklus II mengalami peningkatan sebesar 10,81, terlihat bahwa pembelajaran dengan menggunakan model pembelajaran kooperatif tipe inside-outside circle dapat meningkatkan kemampuan komunikasi matematik siswa.